2006
DOI: 10.1126/science.1127168
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A-Dependent Nuclear Defects in Human Aging

Abstract: Mutations in the nuclear structural protein lamin A cause the premature aging syndrome Hutchinson-Gilford progeria (HGPS). Whether lamin A plays any role in normal aging is unknown. We show that the same molecular mechanism responsible for HGPS is active in healthy cells. Cell nuclei from old individuals acquire defects similar to those of HGPS patient cells, including changes in histone modifications and increased DNA damage. Age-related nuclear defects are caused by sporadic use, in healthy individuals, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

58
1,031
6
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,080 publications
(1,110 citation statements)
references
References 14 publications
58
1,031
6
15
Order By: Relevance
“…These changes are exacerbated by prolonged passage in culture. Interestingly, after passage in culture, cells from aging normal individuals (>80 years) show similar changes in heterochromatin structure as HGPS individuals [98]. In sum, studies of HGPS cells are consistent with the idea that changes in chromatin structurespecifically loss of heterochromatin -may contribute to the aging phenotype.…”
Section: Progeria Cells Exhibit Accelerated Changes In Chromatinsupporting
confidence: 69%
See 1 more Smart Citation
“…These changes are exacerbated by prolonged passage in culture. Interestingly, after passage in culture, cells from aging normal individuals (>80 years) show similar changes in heterochromatin structure as HGPS individuals [98]. In sum, studies of HGPS cells are consistent with the idea that changes in chromatin structurespecifically loss of heterochromatin -may contribute to the aging phenotype.…”
Section: Progeria Cells Exhibit Accelerated Changes In Chromatinsupporting
confidence: 69%
“…HGPS cells show numerous phenotypes, including dramatic defects in nuclear envelope structure, DNA damage and repair defects, changes in gene expression and a reduced rate of proliferation [95]. Fibroblasts from HGPS cells also exhibit epigenetic defects, including decreased abundance of heterochromatic markers, such as histone H3 lysine 9 methylation (H3K9Me) and HP1 proteins [97][98][99]. These changes are exacerbated by prolonged passage in culture.…”
Section: Progeria Cells Exhibit Accelerated Changes In Chromatinmentioning
confidence: 99%
“…Interestingly, it has been shown that the products of this aberrant splicing, the truncated transcript and resultant protein (named progerin), increase in number with aging in HGPS (Goldman et al ., 2004; Cao et al ., 2007; Rodriguez et al ., 2009). In addition, several reports have found progerin, and increasing levels of progerin, in normal cells over the course of normal aging (Scaffidi & Misteli, 2006; McClintock et al ., 2007; Cao et al ., 2007; Rodriguez et al ., 2009), which suggests a similar genetic mechanism in HGPS and normal aging. Moreover, genome‐scale expression profiling in cells from HGPS patients, as well as in physiological aging, has revealed widespread transcriptional misregulation in multiple mammalian tissues (Ly et al ., 2000; Csoka et al ., 2004; Zahn et al ., 2007; Scaffidi & Misteli, 2008; Cao et al ., 2011; McCord et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many characteristics of normal aging appear to be accelerated in individuals with dominant mutations in the LMNA gene encoding A‐type lamins (Ahmed, Ikram, Bibi & Mir, 2017; Apte, Stick & Radmacher, 2017; Cenni et al., 2017; Ikeda et al., 2016; Scaffidi & Misteli, 2006). These include cardiac diseases with a broad range of arrhythmic disturbances, left ventricle dysfunction, and heart failure that show increasing penetrance with age (Captur et al., 2017; Liang, Grogan & Ackerman, 2016).…”
Section: Introductionmentioning
confidence: 99%